2016
DOI: 10.1103/physrevb.93.241402
|View full text |Cite
|
Sign up to set email alerts
|

Surface plasmon polaritons in topological Weyl semimetals

Abstract: We consider theoretically surface plasmon polaritons in Weyl semimetals. These materials contain pairs of band touching points -Weyl nodes -with a chiral topological charge, which induces an optical anisotropy and anomalous transport through the chiral anomaly. We show that these effects, which are not present in ordinary metals, have a direct fundamental manifestation in the surface plasmon dispersion. The retarded Weyl surface plasmon dispersion depends on the separation of the Weyl nodes in energy and momen… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
142
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 135 publications
(153 citation statements)
references
References 62 publications
(97 reference statements)
9
142
0
2
Order By: Relevance
“…Hereafter, we consider a particular value of the dielectric constant, ε b = 13, which was measured in pyrochlore. [17,22] the Drude dielectric function, which is similar to normal metals (NMs). The appearance of Hall current without external magnetic field is known as anomalous Hall effect given by the second term of Eq.…”
Section: Model and Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Hereafter, we consider a particular value of the dielectric constant, ε b = 13, which was measured in pyrochlore. [17,22] the Drude dielectric function, which is similar to normal metals (NMs). The appearance of Hall current without external magnetic field is known as anomalous Hall effect given by the second term of Eq.…”
Section: Model and Methodsmentioning
confidence: 99%
“…As defined before, Ω b = e 2 b/(2π 2 ε 0 ε b ω p ), where b = 0.37Å −1 for pyrochlore [22] and plasmon frequency is given by [17] ω p = 4α 3π…”
Section: Model and Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…[41] showed that the triangle anomaly implies the existence of a new type of collective excitations that stems from the coupling between the density waves of the chiral and electric charges, which was called the chiral magnetic wave (CMW). Furthermore, it was shown that 3D and 2D topologically nontrivial materials host unusual chiral plasmonic modes confined to their surfaces [44,45] or edges [46]. In view of the relativistic-like quasiparticle dispersion in Dirac and Weyl materials, the main properties of their electromagnetic collective excitations should be qualitatively the same as in relativistic plasmas.…”
Section: Introductionmentioning
confidence: 99%